2015
DOI: 10.1097/psy.0000000000000145
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol, Platelet Serotonin Content, and Platelet Activity in Patients With Major Depression and Type 2 Diabetes

Abstract: Increased platelet activity in T2DM and MD may play a role in the association between diabetes, depression, and coronary artery disease. The present data suggest that group differences in cortisol or 5-HT as well as group-specific associations of cortisol or 5-HT with platelet markers might be of limited importance in the shared pathways of T2DM and depression in the pathophysiology of coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 62 publications
1
26
1
Order By: Relevance
“…There are controversial results of blood 5‐HT. Some studies reported that platelet 5‐HT levels did not change in CUMS rats, whereas some studies reported reduced blood 5‐HT levels could be a marker for depression . The present study found there were no noteworthy changes in serum 5‐HT levels of each group.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…There are controversial results of blood 5‐HT. Some studies reported that platelet 5‐HT levels did not change in CUMS rats, whereas some studies reported reduced blood 5‐HT levels could be a marker for depression . The present study found there were no noteworthy changes in serum 5‐HT levels of each group.…”
Section: Discussioncontrasting
confidence: 57%
“…Some studies reported that platelet 5-HT levels did not change in CUMS rats, [30][31][32] whereas some studies reported reduced blood 5-HT levels could be a marker for depression. [34][35][36] The present study found there were no noteworthy changes in serum 5-HT levels of each group. The reason might be related to blood-brain barriers (BBB).…”
Section: Discussionsupporting
confidence: 40%
“…Maximum peripheral serotonin storage is in the platelets (Duerschmied et al., 2013), and dysregulated serotonin signaling in platelets is associated with depression (Ziegelstein et al., 2009). An exploratory study uncovered a correlation between platelet 5‐HT content and increased platelet activity in comorbid patients i.e., with both MDD and T2DM (Zahn et al., 2015). Therefore, both central and peripheral dysregulation of the serotonergic system may link diabetes and depression.…”
Section: Physiological Factors That Play Key Roles In the Comorbiditymentioning
confidence: 99%
“…Studies have shown that many behaviors and physiological changes associated with depression are risk factors for insulin resistance. This includes lower physical activity levels 13 , weight change 14 , and cortisol levels 15 . However, evidence of association between depression and altered glucose homeostasis has been conflicting in epidemiological studies 6, 16 .…”
Section: Discussionmentioning
confidence: 99%